Comparative Analysis of The Modern Edition of The Work “Isharat Аl-Marаm” With The Manuscripts - Saidmuhammadkhon D. Muhibullayev (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This article is devoted to the comparative analysis of the modern editions and manuscripts of the work "Isharatul-Marom". During the research, differences between different editions and manuscripts of the work, changes and revisions in their texts, as well as differences in the meaning and content of the texts were considered. The article aims to understand the historical and cultural context of the work and to identify the annotations and margins written by scholars in the manuscripts.